Evaluation of antileishmanial potential of Gentiana kurroo Royle by in vitro and in silico methods - Arushdeep Sidana, Shiwani Kaushal, Umar Farooq (Journal of Applied Pharmaceutical Science, 2018)
The objective of the present investigation was to evaluate the antileishmanial efficacy of Gentiana kurroo Royle by in vitro assay and in silico molecular docking method. In vitro antileishmanial screening of four different concentrations of the methanolic root extract of G. kurroo was carried out against promastigotes of Leishmania donovani. After in vitro evaluation, a total of 13 already known phyto-constituents present in the methanolic root extract of G. kurroo were docked in silico with five reported drug targets of L. donovani to evaluate their binding and inhibitory potential and to identify the active constituent responsible for antileishmanial activity. The methanolic extract of G. kurroo roots at a dose of 500 μg/ml showed 43.1% inhibition of Leishmania promastigotes after incubation for 24 hours at 25°C. In silico docking analysis of 13 phyto-constituents present in the roots of G. kurroo revealed that gentioside had maximum estimated binding and inhibitory capacity for most of the drug targets followed by norswertianolin. The findings of the present study suggested that these two compounds may be the major players responsible for the in vitro antileishmanial activity and therefore, should be further evaluated to establish their antileishmanial potential against amastigote and promastigote forms of L. donovani.
Keywords: Antileishmanial, Gentianakurroo, in silico docking,Leishmania donovani.